Hippocampal hemispheric and long‐axis differentiation of stimulus content during episodic memory encoding and retrieval: An activation likelihood estimation meta‐analysis. Issue 12 (19th August 2015) - Persson, Jonas; Söderlund, Hedvig
ABSTRACT: While there is ample evidence that the hippocampus is functionally heterogeneous along its longitudinal axis, there is still no consensus regarding its exact organization. Whereas spatial memory tasks frequently engage the posterior hippocampus, the regions engaged during episodic memory are more varying and may depend on the specific nature of the stimuli. Here, we investigate the effect of stimulus content on the location of hippocampal recruitment during episodic memory encoding and retrieval of pictorial and verbal material with a meta‐analysis approach, using activation likelihood estimation and restricting the analysis to the hippocampus. Verbal material was associated with left‐lateralized anterior activation, compared to pictorial material that recruited a more posterior aspect of the hippocampus, primarily within the right hemisphere. This effect held for encoding of both single items and item–item associations but was less clear during retrieval. The findings lend further support to a functional subdivision of the hippocampus along its longitudinal axis and indicate that the content of episodic memories is one factor that determines the location of hippocampal recruitment. © 2015 Wiley Periodicals, Inc.